The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.biopsych.2019.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adoption and Mental Health in Adulthood: The Role of Gene-Environment Correlations and Interactions in the UK Biobank

Abstract: BACKGROUND: Being adopted early in life, an indicator of exposure to early-life adversity, has been consistently associated with poor mental health outcomes in adulthood. Such associations have largely been attributed to stressful environments, e.g., exposure to trauma, abuse, or neglect. However, mental health is substantially heritable, and genetic influences may contribute to the exposure to childhood adversity, resulting in potential genetic confounding of such associations. METHODS: Here, we explored asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Third, we did not investigate the interaction between genetic vulnerability and trauma exposure severity (gene–environment interaction). While of interest to the field, this research question has led to notable non-replications (Assary et al, 2018; Lehto et al, 2019), including no meta-analytic evidence for the interaction between Depression-PRS and childhood trauma (Peyrot et al, 2018). We were also underpowered to detect very small effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not investigate the interaction between genetic vulnerability and trauma exposure severity (gene–environment interaction). While of interest to the field, this research question has led to notable non-replications (Assary et al, 2018; Lehto et al, 2019), including no meta-analytic evidence for the interaction between Depression-PRS and childhood trauma (Peyrot et al, 2018). We were also underpowered to detect very small effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have employed schizophrenia polygenic risk scores to study the possibility of such gene-environment correlations. Increased schizophrenia polygenic risk has been associated with higher paternal age [18], increased likelihood to be adopted [19], and more bullying victimisation [20], each of which is suggestive of a gene-environment correlation [16,21]. Moreover, a recent study found an association between schizophrenia polygenic risk and exposure to trauma in childhood [22], but the extent to which exposure to adversity explains the relationship between schizophrenia liability and mental health problems remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lehto et al. (2020) found that whilst adoptees were found to have worse outcomes across mental health domains, they also displayed a greater genetic predisposition for mental health difficulties. This therefore highlights the complex interactions between genetic risk and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although ACEs are a helpful framework to assess the impact of one's environment on psychological and emotional well-being, stressful environments do not fully explain the link between adoption and mental health. For example, Lehto et al (2020) found that whilst adoptees were found to have worse outcomes across mental health domains, they also displayed a greater genetic predisposition for mental health difficulties. This therefore highlights the complex interactions between genetic risk and environmental factors.…”
mentioning
confidence: 99%